Albumin-Bilirubin Score as A Predictor of Mortality in Patients with Hepatocellular Carcinoma - -, Sagita Adventia; -, Umi Solekhah Intansari; Sianipar, Osman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
An Albumin-Bilirubin (ALBI) score was developed as a tool to assess liver function. Still, its application in clinical practice particularly as a predictor of mortality in hepatocellular carcinoma (HCC)—remains limited. This study aimed to evaluate the ALBI score as a prognostic factor for mortality in patients with HCC. A retrospective cohort study was conducted, involving HCC patients treated at Dr. Sardjito General Hospital, Yogyakarta, from January 2017 to December 2021. Patients with HCC who had an Eastern Cooperative Oncology Group (ECOG) performance status score of 0–2 and available albumin and bilirubin data at the time of diagnosis were included. Subjects were classified into three groups based on ALBI grade: grade I (score ≤ -2.60), grade II (score> -2.60 to ≤ -1.39), and grade III (score > -1.39). The exposed group consisted of subjects with ALBI grade II and grade III, while those with ALBI grade I were classified as the unexposed group. Follow-up was conducted for two years after diagnosis, with death as the primary outcome. Survival analysis was performed using the Kaplan-Meier method and the log-rank test. Hazard ratios (HRs) were analyzed using Cox regression. A p-value of <0.05 was considered statistically significant. The study included 35 subjects with ALBI grade I, 78 with ALBI grade II, and 54 with ALBI grade III. The risk of mortality for subjects with ALBI grade II and grade III was 2.27 and 2.32 times higher, respectively, compared to those with ALBI grade I.